Team resilience in multiple project environments: What characteristics should be explored? - Yuli Eni; Mohammad Ichsan; Ahmad Syamil; Bambang Trigunarsyah (Global Business & Finance Review (GBFR), 2024)
Purpose: This paper aims to explore how project team members' resilience differs based on industry type, project budget, company type, and gender. Design/methodology/approach: Using the conservation of resources theory, this study focuses on exploring the insight of the gathered data from the perspective of descriptive statistics. To achieve this objective, a descriptive analysis was conducted using purposive sampling and snowball techniques, gathering data from 349 respondents. The collected data was analyzed using IBM SPSS software version 25. Findings: The study's results indicate that male respondents are dominant, primarily working in the construction industry, while female respondents tend to work in other industry sectors. Moreover, male respondents exhibited higher resilience scores, but no significant difference in resilience was observed based on gender. However, resil- ience levels varied according to the industry sector. Respondents from industries other than the construction sector tended to display higher resilience. Research limitations/implications: Considering that the study finds only minor variations, businesses in the same industrial sector might think about implementing a practice benchmark. Examining businesses outside of these im- portant industries, however, may provide difficulties. Subsequent data-gathering endeavors may be broadened to encompass more industry sectors and subsequently scrutinized via case studies utilizing smaller samples from certain sectors. Originality/value: This study reveals that it is important to further expand and investigate these insights. Resources for team resilience, such as team confidence, a roadmap for teamwork, the ability to improvise as a team, and psychological safety for the team, can be added to future research. Furthermore, it is crucial to do quantitative research to look at how these elements show up in various industry sectors.
Keywords: 650; resilience; project management; multiple projects; descriptive analysis; project type